Chroni(qu)es new-yorkaises : City Life de Steve Reich - Antoine CAZÉ (E-REA)
This article analyzes Steve Reich’s City Life, a 1995 piece in which the American composer blends noises and voices he recorded on the streets in New York City with the sounds of an instrumental ensemble. We try to demonstrate that in spite of appearances, Reich does not merely propose a soundscape of the city or attempt to fit any preconceived sound rendition of a city; rather, we argue that through this work, he develops a properly political practice and theory of the city allowing him to go further in the direction he first explored back in the 1960s with It’s Gonna Rain. Along the lines of his customary composition techniques involving repetition and phasing, Reich has build City Life as a transposition of the multiple and asynchronous temporalities characterizing a city: his chronicle of New York sounds thus becomes a real chronotope allowing him to give back its voice to the urban community while offering a fresh perspective upon the classical music concert as it relates with the city space in which it takes place.